1983
DOI: 10.1002/crat.2170180314
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of free carriers in high‐conducting n‐GaN

Abstract: Growth experiments with GaN in the system Ga/HCl/NHJHe at different growth temperatures show that the assumption of N-vacancies t o be responsible for the high n-conductivity is questionable. The dependence of carrier concentration on growth temperature as well as the decrease in carrier concentration when additionally purified NH, is used indicate that donor impurities are incorporated. The most probable impurity is oxygen, substitutionally incorporated onto N-sites. The observed growth rate dependence of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(49 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…In Ref. [8] injection of H 2 O during growth lead to higher [19], whereas as shown above the residual donor level is much shallower than the L1 -L4 levels.…”
Section: Discussionmentioning
confidence: 76%
“…In Ref. [8] injection of H 2 O during growth lead to higher [19], whereas as shown above the residual donor level is much shallower than the L1 -L4 levels.…”
Section: Discussionmentioning
confidence: 76%
“…12 Oxygen had been proposed as a potential source of n-type conductivity in GaN as early as 1983. 24 Still, the prevailing conventional wisdom, attributing the n-type behavior to nitrogen vacancies, proved hard to overcome. Recent experiments have confirmed that unintentionally doped n-type GaN samples contain silicon or oxygen concentrations high enough to explain the electron concentrations.…”
Section: Unintentional Doping -Oxygenmentioning
confidence: 99%
“…As early as 1983, oxygen had been proposed as a potential source of n-type conductivity in GaN [14]. In 1992, Chung and Gershenzon observed the effect of oxygen on the electrical and optical properties of GaN grown by MOCVD [15].…”
Section: Nitrogen Vacancies Versus Unintentional Impuritiesmentioning
confidence: 99%